Architecture of Providing Services in Intelligent Transportation Systems Using Semantically Defined Information - Hrkut, Patrik (Communications - Scientific Letters of the University of Zilina, 2010)
Intelligent transportation systems (ITS) is an area currently developing very fast. The key to the ITS success will definitely be the implementation of services which would be solving all of the requirements of the road transportation participants. The article proposes the architecture to be used to control the services provided within the intelligent transportation systems. The architecture presupposes using semantically modelled information to be able to find new services in more intelligent way, to preliminarily distinguish unknown services and use them anyway.
Keywords: no keywords